2015
DOI: 10.3390/math3030781
|View full text |Cite
|
Sign up to set email alerts
|

Algebra of Complex Vectors and Applications in Electromagnetic Theory and Quantum Mechanics

Abstract: A complex vector is a sum of a vector and a bivector and forms a natural extension of a vector. The complex vectors have certain special geometric properties and considered as algebraic entities. These represent rotations along with specified orientation and direction in space. It has been shown that the association of complex vector with its conjugate generates complex vector space and the corresponding basis elements defined from the complex vector and its conjugate form a closed complex four dimensional lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Multiplication of Equation (14) by ρ and Equation (15) below by L 1 , addition of the resulting equations [29], and using the ordinary product rule of differential multivariable calculus a form as in Equation (16) is obtained whereby a is given by a = ρ L 2 .…”
Section: A Solution Procedures For δ Arbitrarily Small In Quantitymentioning
confidence: 99%
See 2 more Smart Citations
“…Multiplication of Equation (14) by ρ and Equation (15) below by L 1 , addition of the resulting equations [29], and using the ordinary product rule of differential multivariable calculus a form as in Equation (16) is obtained whereby a is given by a = ρ L 2 .…”
Section: A Solution Procedures For δ Arbitrarily Small In Quantitymentioning
confidence: 99%
“…An imaginary vector is defined as a sum of two real vectors one of which is multiplied by the complex number i. If we take the complex number i and replace it by a pseudo-scalar I in the context of Geometric Algebra it can be shown that for compressible flow the density appearing in the Navier-Stokes equations can be written in terms of a "complex" exponential function in time or, even better, an exponential of a multivector which can be proven to be well defined [14]. The form of a complex vector has been used as a bivector to study polarization of electric fields [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexification process, in general, provides a pathway for generating higher dimensional geometric algebra from lower dimensions. This is explicitly illustrated through examples in the work of Muralidhar [7] (2)…”
Section: Aperiodic Internal Space and Clifford Motorsmentioning
confidence: 99%
“…Recently, the role of spin and the internal charged particle structure in complex vector formalism have been studied by the author. [23][24][25] In the presence of zeropoint field, an elementary charged particle oscillates in accordance with the oscillations of the random zeropoint field and an average of all such oscillations may be considered as complex rotations and the imaginary part of such complex rotation gives the classical origin of particle spin. 26,27 It has been shown that the mass of the particle may be interpreted to the zeropoint field energy associated with the local complex rotation or oscillation confined in a region of space of the order of Compton wavelength.…”
mentioning
confidence: 99%